Immediate Implant with simultaneous Ridge Augmentation - Saurabh Chaturvedi; Mohammed A Alfarsi; Mudita Chaturvedi; Kaushik Pandey; Sunil Kumar Vaddamanu (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
The Ultimate goal of prosthetic replacement following teeth loss, is to provide a functional restoration that is harmonious with the remaining natural dentition .To achieve this goal hard and soft tissues should be properly healed with good quality and adequate volume. In the anterior maxilla the degree of horizontal bone resorption in post extraction site is nearly twice as high as that of vertical bone resorption during fi rst month. An increasingly common strategy is to preserve bone that includes the placement of dental implant into fresh extraction site. Immediate implant placement reduces the amount of time anticipated for loading and the number of surgical interventions which in turn yields higher patient's satisfaction. Finally elimination of the wait period for primary healing of the soft tissues and regeneration of osseous structure signifi cantly shortens the overall treatment time and transitional state without teeth. This short communication about immediate implant case refl ects upon several steps followed for an immediate placement of dental implant in fresh extraction socket and outlines its advantages.